PERTUMBUHAN, HASIL DAN TOLERANSI GENOTIP PADI TERHADAP PENYAKIT HAWAR DAUN (Bacterial Leaf Blight) PADA APLIKASI DOSIS Paenibacillus Polymixa BERBEDA - Ai Komariah; Eva Lady Mustika (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2016)
The research was to study the effect of genotype rice plants and Paenibacillus Polymixa dose to growth, yields and genotype tolerances to BLB (Bacterial Leaf Blight) deseases.The research was conducted in the village Kedawung Majalaya Karawang District of West Java in the rainy season, from Januari 2015 until Mei 2015. The experiment was used Strip plots design with genotypes of rice was the main plot consist of Sri Putih (v1), Manohara (v2) and IR 64 (v3), subplots were doses paenybacilus polymixa (d1 ) Dose Paenybacillus polymixa 0 liters / ha, (d2) Dose Paenybacillus polymixa 2.5 liters / ha (5 ml / liter), (d3) Dose Paenybacillus polymixa 5 liters / ha (10 ml / liter) and (d4) Dose Paenybacillus pol ymixa 7.5 liters / ha (15 ml / liter). The results of the experiment shosed that no interaction between the administration of the dose variation Paenybacillus polymixa with genotype rice plants against rice yields and not interaction between administration of the dose variation Paenybacillus polymixa with genotype rice plants to suppress the intensity of the attack Bacterial leaf blight disease. For the intensity of the disease, dose applications Paenybacillus polymixa 2.5 liters / ha (5 ml / liter) was effectively used during the vegetative age of 21, 28 and 35 days after planting.